2019
DOI: 10.7899/jce-17-26
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of student performance and satisfaction between a traditional and integrative approach to teaching an introductory radiology course on the extremities

Abstract: Objective: The purpose of the study was to compare student performance and student satisfaction ratings for an introductory extremities radiology course taught using 2 different educational methods. Methods: One group of students was taught using a traditional face-to-face instruction method, and the other group received an integrative blended-learning approach. A multivariate analysis of scores on lecture and laboratory exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(70 reference statements)
2
7
0
Order By: Relevance
“…Of the 56 studies, 47 were conducted in high-income countries: 14 were from the United States [ 9 , 10 , 29 , 31 , 36 , 38 , 43 , 50 , 53 - 55 , 59 , 61 , 73 ], 2 from Canada [ 47 , 58 ], 5 from Germany [ 39 , 41 , 46 , 57 , 76 ], 3 from the United Kingdom [ 42 , 56 , 75 ], 3 from Spain [ 30 , 45 , 48 ], 1 from France [ 74 ], 1 from Greece [ 34 ], 1 from Sweden [ 67 ], 1 from the Netherlands [ 37 ], 1 from Korea [ 40 ], 1 from Poland [ 79 ], 1 from Serbia [ 70 ], 1 from Croatia [ 64 ], 1 from Turkey [ 32 ], 2 from Taiwan [ 28 , 51 ], 1 from Japan [ 69 ], and 7 from Australia [ 44 , 49 , 63 , 65 , 66 , 68 , 78 ]. Of the 56 studies, 9 studies were conducted in low- or middle-income countries: 2 from Thailand [ 52 , 62 ], 1 from China [ 77 ], 1 from Malaysia [ 72 ], 2 from Iran [ 27 , 71 ], 1 from Jordan [ 35 ], 1 from South Africa [ 11 ], and 1 from Uruguay [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 56 studies, 47 were conducted in high-income countries: 14 were from the United States [ 9 , 10 , 29 , 31 , 36 , 38 , 43 , 50 , 53 - 55 , 59 , 61 , 73 ], 2 from Canada [ 47 , 58 ], 5 from Germany [ 39 , 41 , 46 , 57 , 76 ], 3 from the United Kingdom [ 42 , 56 , 75 ], 3 from Spain [ 30 , 45 , 48 ], 1 from France [ 74 ], 1 from Greece [ 34 ], 1 from Sweden [ 67 ], 1 from the Netherlands [ 37 ], 1 from Korea [ 40 ], 1 from Poland [ 79 ], 1 from Serbia [ 70 ], 1 from Croatia [ 64 ], 1 from Turkey [ 32 ], 2 from Taiwan [ 28 , 51 ], 1 from Japan [ 69 ], and 7 from Australia [ 44 , 49 , 63 , 65 , 66 , 68 , 78 ]. Of the 56 studies, 9 studies were conducted in low- or middle-income countries: 2 from Thailand [ 52 , 62 ], 1 from China [ 77 ], 1 from Malaysia [ 72 ], 2 from Iran [ 27 , 71 ], 1 from Jordan [ 35 ], 1 from South Africa [ 11 ], and 1 from Uruguay [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies focusing on computer-assisted instruction blended learning, 5 [ 10 , 11 , 48 , 49 , 73 ] of the 8 studies [ 9 - 11 , 38 , 48 , 49 , 52 , 73 ] showed significantly higher scores than those of traditional learning. Only 1 study [ 38 ] showed a significant negative effect compared to traditional learning (standard mean difference –0.68, 95% CI –1.32 to –0.04).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies focusing on computer-assisted instruction blended learning, 5 [10,11,48,49,73] of the 8 studies [9][10][11]38,48,49,52,73] showed significantly higher scores than those of traditional learning. Only 1 study [38] showed a significant negative effect compared to traditional learning (standard mean difference -0.68, 95% CI -1.32 to -0.04).…”
Section: Computer-assisted Instruction Blended Learning Versus Traditional Learningmentioning
confidence: 99%
“…Dentistry studies included 3 online blended learning studies (standard mean difference 0.37, 95% CI 0.14 to 0.64, z=2. 63 [34,36,38,39,41,43,44,46,47,50,53,64,[69][70][71][72]74,78], and in computer-aided-instruction (standard mean difference 2.1, 95% CI 0.68 to 3.44, z=2.91, I 2 =97.9%, n=706) [11,38,48,49,73] suggesting more positive effects of blended learning over traditional learning alone for learning in medicine.…”
Section: Sensitivity Analysesmentioning
confidence: 99%